Dendritic Growth: classical models and constructal analysis - Miguel, A. F. (2012)
Shape and structure play a fundamental role in models used for “per-ceiving” and “understanding” nature. These aspects are so basic and familiar to various fields of natural sciences that we tend to take them for granted.Dendritic (from the Greek dendron that means tree) structures are very common in nature. Examples can be found in almost every field of today’s scientific interest: in physics and chemistry, zoology and botanic, biology, earth sciences, and even in self-organization phenomena that occur in traffic systems such as the patterns of motion developed by pedestrians and ants. Do these patterns result from any special cause? Is there any unifying picture in which they share similar underlying principles? Bearing the previous questions in mind, and attempting to find an-swers, some classical methodologies available to describe dendritic growth phenomenon are reviewed, and a new alternative meth-odology is also presented based on the constructal principle.